Prognostic Factors for Tumor Recurrence after a 12-Year, Single-Center Experience of Liver Transplantations in Patients with Hepatocellular Carcinoma. (4th August 2010) - Cescon, Matteo; Ravaioli, Matteo; Grazi, Gian Luca; Ercolani, Giorgio; Cucchetti, Alessandro; Bertuzzo, Valentina; Vetrone, Gaetano; Del Gaudio, Massimo; Vivarelli, Marco; D'Errico-Grigioni, Antonietta; Dazzi, Alessandro; Di Gioia, Paolo; et al.
Abstract : Background . Factors affecting outcomes after orthotopic liver transplantation (OLT) for hepatocellular carcinoma (HCC) have been extensively studied, but some of them have only recently been discovered or reassessed. Methods . We analyzed classical and more recently emerging variables with a hypothetical impact on recurrence-free survival (RFS) in a single-center series of 283 patients transplanted for HCC between 1997 and 2009. Results . Five-year patient survival and RFS were 75% and 86%, respectively. Thirty-four (12%) patients had HCC recurrence. Elevated preoperative alpha-fetoprotein (AFP) levels, preoperative treatments of HCC, unfulfilled Milan and up-to-seven criteria at final histology, poor tumor differentiation, and tumor microvascular invasion negatively affected RFS by univariate analysis. Milan and up-to-seven criteria applied preoperatively, and the use of m-TOR inhibitors did not reach statistical significance. Cox's proportional hazard model showed that only elevated AFP levels (OddsRatio = 2.88 ; 95% C . I . = 1.43 –5.80;P = .003 ), preoperative tumor treatments (OddsRatio = 4.84 ; 95% C . I . = 1.42 –16.42;P = .01 ), and microvascular invasion (OddsRatio = 4.82 ; 95% C . I . = 1.87 –12.41;P = .001 ) were predictors of lower RFS. Conclusions . Biological aggressiveness and preoperative tumor treatment, rather than traditional and expanded dimensional criteria, conditioned the outcomes in patients transplanted for HCC.